URGENSI DAN KONSEKUENSI PEMBACAAN SIGHAT TAKLIK TALAK SETELAH AKAD NIKAH PERSPEKTIF HUKUM ISLAM - Yuda Maulana (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
The aim of this research is to find out and understand the urgency and consequences of reading the sighat taklik talak after the marriage contract in a marriage from an Islamic legal perspective. The research method used in this research is a qualitative research approach (Qualitative research), with a library method (Library research). The results and discussion of this research are that there is no legal basis that strictly requires the groom to pronounce the sighat taklik talak after the marriage ceremony, but rather it is a choice or voluntary choice on the part of the groom himself. However, if the divorce agreement has been agreed upon, it cannot be revoked. The existence of divorce taklik is a form of protection of the wife's rights against the husband's arbitrariness in the household. So the right to divorce which basically rests with the husband can also be owned by the wife if in the future the husband denies the contents of the divorce agreement. However, in order for the divorce to actually occur, the wife must report the matter to the Religious Court and pay iwadh as ransom for her husband so that it can then be processed and receive a decision from the judge that the divorce is due to the wife in the name of the husband.